A survey on Islamic Websites for children - Kh. Abdulatif, Zaidoon; Ayif, Mustafa Nasser; Mahmud, Murni (IIUM Press, 2011)
Websites are becoming pervasive for children in the last decade regarding for different uses and purposes which may include educational, entertainments, shopping or casual surfing to find infonnation. Children are learning to use computers and the internet at a very young age, which makes most of the family encourage their children to use particular websites for their age. In this chapter we are conducting a study of Islamic websites for children by online survey to compare three children Islamic website in order to see what is the main focus based on users' idea.